Preliminary feasibility study using a solution of synthetic enzymes to replace the natural enzymes in polyhemoglobin-catalase-superoxide dismutase-carbonic anhydrase: effect on warm ischemic hepatocyte cell culture - Hoq, M.; Chang, T. M. S. (Frontiers in Bioengineering and Biotechnology, 2023)
This is a study on a simple solution of chemically prepared small chemical molecules of synthetic enzymes, catalase. superoxide dismutase and carbonic anhydrase (CAT, SOD, CA). We carried out study to see if these synthetic enzymes can replace the natural enzymes (CAT, SOD, CA) and avoid the need for the complicated cross-linking of natural enzymes to polyHb to form PolyHb-CAT-SOD-CA. We compared the effect a solution of these 3 synthetic enzymes on the viability of warm-ischemic hepatocytes that were exposed to nitrogen for one hour at 37°C. PolyHb significantly increased the viability. The 3 synthetic enzymes themselves also significantly increased the viability. The use of both PolyHb and the 3 synthetic enzymes resulted an additive effect in the recovery of viability. Increasing the concentration of the synthetic enzymes result in further increase in the effect due to the. synthetic enzymes IMPLICATION In addition to polyHb there are a number of other HBOCs oxygen carriers. However, only Biopure's HBOC product has received regulatory approval but only in Russian and South Africa. None of the HBOCs have received regulatory approval by other countries. If regulatory agencies require HBOCs to have antioxidant property or CO2 transport property, all is needed is to add or inject the solution of synthetic enzymes as a separate component.